PD-L1 Expression in Premalignant and Malignant Trophoblasts From Gestational Trophoblastic Diseases Is Ubiquitous and Independent of Clinical Outcomes. Issue 3 (March 2017) - Bolze, Pierre-Adrien; Patrier, Sophie; Massardier, Jérôme; Hajri, Touria; Abbas, Fatima; Schott, Anne Marie; Allias, Fabienne; Devouassoux-Shisheboran, Mojgan; Freyer, Gilles; Golfier, François; You, Benoît
Abstract : Objective: Recently reported expression of programmed cell death 1 ligand 1 (PD-L1) in gestational trophoblastic diseases (GTDs) suggests that the immune tolerance of pregnancy might be hijacked during neoplastic process. We assessed PD-L1 protein expression in premalignant and malignant GTD lesions and analyzed associations with disease severity and chemotherapy outcomes. Methods: We included 83 GTD whole-tissue sections from 76 patients in different treatment settings. PD-L1 protein expression was assessed with immunohistochemistry in each trophoblast subtype with the Allred total score (ATS), which combines intensity and proportion expression on a 0- to 8-point scale. Peritumoral immune infiltrate was scored on hematoxylin-eosin-safran–stained slides. Results: PD-L1 expression was ubiquitous and strong in all GTD trophoblast subtypes. For invasive moles, ATS scores were maximal at 8 in 100%, 100%, and 75% of syncytiotrophoblast, villous cytotrophoblast, and extravillous cytotrophoblast specimens, respectively. For choriocarcinomas, ATS was 8 in 80% of specimens. Immune infiltrates were moderate to severe in 61%, 100%, and 100% of peritumoral zones of choriocarcinoma, epithelioid trophoblastic tumor, and invasive moles, respectively. Because of the homogeneous pathological findings, no significant differences in PD-L1 expression profiles or peritumoral immune infiltrates were found regarding FIGO (International Federation of Gynecology Obstetrics) prognostic score, fatal outcome, or chemosensitivity. Conclusions: We confirm that PD-L1 is constitutively expressed in all GTD premalignant and malignant trophoblast subtypes, independently from FIGO score, chemoresistance, or fatal outcomes, thereby suggesting a crucial role for PD-L1 in the development and tolerance of GTD. Assessment of anti–PD-L1 drug in GTD patients has been activated. Abstract : Supplemental digital content is available in the text.